2012
DOI: 10.1371/journal.pone.0034609
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human and Soil Candida tropicalis Isolates with Reduced Susceptibility to Fluconazole

Abstract: Infections caused by treatment-resistant non-albicans Candida species, such as C. tropicalis, has increased, which is an emerging challenge in the management of fungal infections. Genetically related diploid sequence type (DST) strains of C. tropicalis exhibiting reduced susceptibility to fluconazole circulated widely in Taiwan. To identify the potential source of these wildly distributed DST strains, we investigated the possibility of the presence in soil of such C. tropicalis strains by pulsed field gel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 39 publications
0
52
0
1
Order By: Relevance
“…The rates of isolation of C. krusei, C. guilliermondii, C. lusitaniae, C. kefyr, and C. famata did not vary significantly, whereas those of fluconazole-resistant species C. rugosa, C. inconspicua, and C. norvegensis increased 5-to 10-fold over the 10.5-year study period [20]. It is worth noting that C. tropicalis isolates from Taiwan hospitals and soil samples, revealed strains with reduced susceptibility to azole drugs, which can be of great clinical importance [21]. The isolates recovered from humans and soil, originating from different geographic regions of Taiwan, share the same genome pattern (diploid sequence type).…”
Section: 47mentioning
confidence: 92%
“…The rates of isolation of C. krusei, C. guilliermondii, C. lusitaniae, C. kefyr, and C. famata did not vary significantly, whereas those of fluconazole-resistant species C. rugosa, C. inconspicua, and C. norvegensis increased 5-to 10-fold over the 10.5-year study period [20]. It is worth noting that C. tropicalis isolates from Taiwan hospitals and soil samples, revealed strains with reduced susceptibility to azole drugs, which can be of great clinical importance [21]. The isolates recovered from humans and soil, originating from different geographic regions of Taiwan, share the same genome pattern (diploid sequence type).…”
Section: 47mentioning
confidence: 92%
“…Unfortunately, acquired fluconazole resistance is increasing, with ranges from approximately 7% in Denmark (9) to 9% in a global study (11) and 40% in Japan (12). Based on such findings, echinocandins are increasingly being utilized in the management of candidiasis caused by C. tropicalis (10,(13)(14)(15).…”
mentioning
confidence: 99%
“…Thus, calcineurin is, in general, required for the virulence of C. tropicalis and C. dubliniensis in both murine systemic and ocular infection models, while Crz1 is required for the virulence of C. tropicalis and C. dubliniensis only in a murine systemic infection model and not in an ocular infection model, suggesting a specific niche requirement (bloodstream versus ocular surface) of Crz1 in both C. tropicalis and C. dubliniensis (27). In addition to being frequently isolated from patients (11,17,(60)(61)(62), C. tropicalis has also been isolated from the mouse intestine (where it constitutes up to 65% of the overall fungal component) (63) and environmental compost and soil (11,64). Previous studies suggest that C. tropicalis can be transferred by hand-tohand contact (65), indicating a potential route for human-human transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Within the last few years, C. tropicalis drug-tolerant or -resistant isolates have frequently been isolated from patients and environmental samples (10)(11)(12)(13)(14). For example, Garcia-Effron et al showed that 7.5% (3/40) of clinical C. tropicalis isolates were caspofungin resistant owing to amino acid substitutions in beta-1,3-glucan synthase (Fks1p) that resulted in caspofungin-based therapy failures (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation